Nitrites and nitrates from food additives and natural sources and cancer risk: results from the NutriNet-Santé cohort. (18th March 2022) - Chazelas, Eloi; Pierre, Fabrice; Druesne-Pecollo, Nathalie; Esseddik, Younes; Szabo de Edelenyi, Fabien; Agaesse, Cédric; De Sa, Alexandre; Lutchia, Rebecca; Gigandet, Stéphane; Srour, Bernard; Debras, Charlotte; Huybrechts, Inge; et al.
Abstract: Background: Nitrates and nitrites occur naturally in water and soil. They are also used as food additives (preservatives) in processed meats. They could play a role in the carcinogenicity of processed meat. The objective was to investigate the relationship between nitrate and nitrite intakes (natural food, water and food additive sources) and cancer risk in a large prospective cohort with detailed dietary assessment. Methods: Overall, 101    056 adults from the French NutriNet-Santé cohort (2009–ongoing, median follow-up 6.7 years) were included. Nitrites/nitrates exposure was evaluated using repeated 24-h dietary records, linked to a comprehensive composition database and accounting for commercial names/brands of industrial products. Associations with cancer risk were assessed using multi-adjusted Cox hazard models. Results: In total, 3311 incident cancer cases were diagnosed. Compared with non-consumers, high consumers of food additive nitrates had higher breast cancer risk [hazard ratio (HR) = 1.24 (95% CI 1.03–1.48), P  = 0.02], more specifically for potassium nitrate. High consumers of food additive nitrites had higher prostate cancer risk [HR = 1.58 (1.14–2.18), P  = 0.008], specifically for sodium nitrite. Although similar HRs were observed for colorectal cancer for additive nitrites [HR = 1.22 (0.85–1.75)] and nitrates [HR = 1.26 (0.90–1.76)], no association was detected, maybe due to limited statistical power for this cancer location. No association was observed for natural sources. Conclusion: Food additive nitrates and nitrites were positively associated with breast and prostate cancer risks, respectively. Although these results need confirmation in other large-scale prospective studies, they provide new insights in a context of lively debate around the ban of these additives from the food industry.